Pengetahuan dan Sikap Berhubungan dengan Resiko Tertular Covid-19 pada Masyarakat Sulawesi Utara : Knowledge and Attitudes Related to the Risk of Contracting COVID-19 in the Community of North Sulawesi - Erika Emnina Sembiring; Maria Lupita Nena Meo (Fakultas Keperawatan Universitas Andalas, 2020)
Coronavirus Disease 2019 (Covid-19) has become a pandemic worldwide, including in Indonesia. The transmission of Covid-19 in Indonesia is very fast and affects 34 provinces, many of which are in red zones. North Sulawesi is one of the provinces with a very fast Covid-19 transmission. Public knowledge and attitudes towards the Covid-19 pandemic are very important to reduce the risk of infection among the community. The purpose of this study was to determine the relationship between knowledge and attitudes with the risk of contracting Covid-19 in the people of North Sulawesi. The research design used was descriptive correlation with cross sectional approach, with a sample size of 400 respondents who were selected using the consecutive sampling method. Data collection used a google form questionnaire and analyzed using Fisher's Exact Test. The results showed that there was a relationship between knowledge and attitudes with the risk of contracting Covid 19 in the people of North Sulawesi with a p value (0.000). Good knowledge and a positive attitude from the public in dealing with the Covid-19 pandemic can make people take real action to reduce the risk of contracting Covid-19.